Mechanical Cell-to-Cell Interactions as a Regulator of Topological Defects in Planar Cell Polarity Patterns in Epithelial Tissues - Markovič, Rene; Marhl, Marko; Gosak, Marko (Frontiers in Materials, 2020)
A precise structural organization of epithelial cells is needed for the proper functioning and development of different tissues. The epithelial cell packing mechanism is associated with mechanical interactions between cells that place the tissue in a state of the lowest mechanical energy. In addition, the planar cell polarity has been recognized as another important mechanism for the epithelial organization that ensures the orientational ordering of the cells. Planar cell polarity is a consequence of an asymmetric distribution of certain transmembrane proteins which is driven by specific intracellular signaling pathways. Mutations and other disruptions of these pathways were found to cause an impaired cytoarchitecture of the epithelium layer. Mutant cells with disrupted activities of signaling proteins basically represent topological defects, which can lead to dysfunctions in tissue operation. Motivated by the fact that regional variations of bond tensions were found in the vicinity of mutant cells, we implement a computational model that combines the tissue development processes following the concept of mechanical energy minimization and the intracellular polarization. Our results reveal that a decrease in mechanical interactions between normal and mutant epithelium cells represents a conceivable regulatory mechanism that diminishes the impact of topological defects caused by mutant cells.